ANALISIS PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR CAMAT SINEMBAH TANJUNG MUDA HULU - Utami, Dian; Batubara, Soulthan Saladin; Ario, Firman (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
The research analysis aims to analyze the influence of organizational culture and competence on the performance of employees at the Sinembah Tanjung Muda Hulu District Head Office. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This research uses multiple linear regression analysis. The sample in this study was 37 respondents. Primary data collection uses a questionnaire. The results of the research show that the test results for the organizational culture variable show a tcount value of 2.964 > ttable of 2.03 with a significant value of 0.005 <0.05, so hypothesis H1 is accepted and H0 is rejected, meaning that organizational culture has a partially positive and significant effect on the performance of the employees of the Sinembah Tanjung Muda Hulu District Head Office. The test results for the competency variable show a tcount value of 5.161 > ttable of 2.03 with a significant value of 0.00 <0.05, so the hypothesis H2 is accepted and H0 is rejected, meaning that competency has a partially positive and significant effect on the performance of employees at the Sinembah Tanjung Muda Hulu District Head Office. The results of the simultaneous hypothesis test or F test prove that the calculated F value is 71.841 which is greater than 3.28 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that H3 is accepted and H0 is rejected so it can be concluded that organizational culture and compensation have a significant simultaneous effect on the performance of employees at the Sinembah Tanjung Muda Hulu District Head Office.